Peace Journalism and News Coverage on the Cyprus Conflict - Ersoy, Metin (The Muslim World, 2010)
[Abstract Not Available]
Keywords: Peace Journalism; News Media; News Coverage; News Coverage; Cyprus Conflict; News Framing